A new approach for estimating leagile decoupling point using data envelopment analysis. Issue 3 (1st August 2016) - Shahin, Arash; Gunasekaran, Angappa; Khalili, Azam; Shirouyehzad, Hadi
Abstract : Purpose: To propose a new approach for determining decoupling point in leagile chain, based on lean and agile criteria regarding market and customer demands and internal capabilities of the chain with the ultimate goal of fulfilling customer needs and increasing chain profit. Design/methodology/approach: In the new approach, lean and agile criteria have been defined for assessing the effectiveness and efficiency of supply chain. The efficiency and effectiveness ratios have been calculated for lean and agile processes using input oriented and output oriented BCC methods, respectively. Based on the results, inefficient and ineffective units have been addressed and the decoupling point has been determined. Findings: Findings indicate that decoupling point can be regarded as a border line between two strategies of lean and agile production, and fuzzy decoupling point and also lean-agile distance can provide the basis for distinguishing the two strategies. Practical implications: Determining decoupling point has an important role in dynamic performance of a supply chain. By the proposed approach, managers can estimate the most probable area for decoupling point. Moreover, by appropriate determination of decoupling point, an organization can increase its public responsibility by appropriate usage of its resources and faster responding to customers' requirements. Originality/value: In this study, in addition to determining a decoupling point in a supply chain with the aim of increasing productivity, the subject of leagile strategy of supply chains has been developed.